2016
DOI: 10.1189/jlb.3a0116-032rr
|View full text |Cite
|
Sign up to set email alerts
|

VIP impairs acquisition of the macrophage proinflammatory polarization profile

Abstract: This study tested the hypothesis that vasoactive intestinal peptide (VIP) is able to modify the macrophage inflammatory profile, thus supporting its therapeutic role in autoimmune diseases. Macrophages are innate immune cells that display a variety of functions and inflammatory profiles in response to the environment that critically controls their polarization. Deregulation between the pro- and anti-inflammatory phenotypes has been involved in different pathologies. Rheumatoid arthritis (RA) is an autoimmune d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 41 publications
1
34
0
Order By: Relevance
“…VIP expression has also been described in human eosinophils [30] and in eosinophils of granulomatous lesions induced by infection with Schistosomiasis mansoni [31]. We reported that neither M1 nor M2 human macrophages express transcripts of VIP [32]. Concerning cells of a lymphoid lineage, in the 1990s, our team reported, for the first time, the synthesis and secretion of VIP in murine T and B lymphocytes [33][34][35].…”
Section: Biological Characteristics Of Vipmentioning
confidence: 80%
See 1 more Smart Citation
“…VIP expression has also been described in human eosinophils [30] and in eosinophils of granulomatous lesions induced by infection with Schistosomiasis mansoni [31]. We reported that neither M1 nor M2 human macrophages express transcripts of VIP [32]. Concerning cells of a lymphoid lineage, in the 1990s, our team reported, for the first time, the synthesis and secretion of VIP in murine T and B lymphocytes [33][34][35].…”
Section: Biological Characteristics Of Vipmentioning
confidence: 80%
“…Upregulated levels of pro-inflammatory mediators, including TNF-α, IL-6, and CXCL8 and CCL2 chemokines, in polyclonally stimulated peripheral blood lymphocytes from RA patients were reduced after treatment with VIP [167]. Furthermore, regarding its effects on macrophages, VIP was able to impair the acquisition of the pro-inflammatory polarization profile described for macrophages in RA synovium, favoring instead an anti-inflammatory phenotype [32]. Additionally, the involvement of VIP in the modulation of Th subsets has been extensively studied, as previously detailed.…”
Section: Vip In Rheumatoid Arthritismentioning
confidence: 90%
“…Among them, one subpopulation showed increased expression of genes associated with anti-inflammatory macrophages, such as Ccl8, Folr2, C1qa and Mrc1, and was named anti-inflammatory macrophages (AIM). (35,36) Another subset characterized by elevated expression of pro-inflammatory genes (Ptgs2, Ccl3, Inhba, Nos2) was named pro-inflammatory macrophages (PIM) (37,38). The monocyte subset (Mono) was characterized by increased expression of genes like Ly6c2 and Plac8 (Fig.…”
Section: Macrophage Heterogeneity and Their Down-regulation By Scaffoldsmentioning
confidence: 99%
“…VIP inhibits the production of proinflammatory cytokines such as tumor necrosis factor α (TNFα), IL-6, IL-12, iNOS, and promotes the production anti-inflammatory cytokines such as IL-10[ 148 - 153 ]. VIP also inhibits the transcription factors AP-1, nuclear factor-κB (NFκB), CREB, and IRF-1[ 142 , 147 , 153 , 154 ], and impairs the acquisition of the macrophage proinflammatory polarization profile[ 155 ].…”
Section: Interactions Between the Gi Nes And The Immune Systemmentioning
confidence: 99%